Interpersonal Communication of Visually Impaired Baristas with Customers: Case Study at Café More Wyataguna Bandung City - Rahmayani, Audina; Nugroho, Catur (Future Science, 2024)
This article examines interpersonal communication between baristas with visual impairments and customers in coffee shops. The research used a case study at Café More, Bandung, Indonesia, which Wyata Guna Special School manages. The research sought to reveal how visually impaired baristas interact and communicate with the coffee shop customers, most of whom do not have disabilities. The study focuses on the communication behavior of low-vision baristas in the form of oral, written, and non-verbal communication. Using the qualitative method and case study approach, the researcher conducted in-depth interviews with two baristas with visual impairment as critical informants, five customers and a manager of Café More as primary informants, and two people with visual impairment who are also customers of Café More as supporting informants. The results of the study found that the blind barista of Low Vision Café More Bandung conducted two communications, namely verbal communication and nonverbal communication. Verbal communication between blind baristas and customers at Café More Bandung goes well even though it requires repetition of customer speech to ensure the messages are conveyed correctly because most supporting informants are regular customers. In nonverbal communication in research, namely a gesture or body movement and hand movements such as using fingers to determine the number of orders. With this research, it is hoped that people with disabilities will get the same place in jobs that require interaction and communication with consumers.